Development of biomedical data acquisition system in hard real-time Linux environment - Alam, Marzia Ruman; Azad, AKM Abdul Malek (© 2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2012 International Conference on Biomedical Engineering, ICoBE 2012; Penang; Malaysia; 27 February 2012 through 28 February 2012 [© 2012 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/ICoBE.2012.6179053